Effectiveness of the CAMPE module for preeclampsia prevention among high-risk pregnant women - Bundu, Sitti Mukarramah; Amdadi, Zulaeha Amiruddin; Beddu, Suriani; Manjilala, Manjilala; Lorica, Joshepine Daquigaq; Sabilah, Hanifah (Universitas Aisyiyah Yogyakarta, 2025)
Preeclampsia remains one of the leading causes of maternal mortality in Indonesia. Prevention efforts through nutrition education based on local foods are considered effective in reducing the risk. This study aimed to develop, assess the feasibility of the module through expert validation and evaluate the effectiveness of the CAMPE (Cara Mencegah Preeklamsia-Prevent Preeclampsia through Nutritional Management) Module for high-risk pregnant women in Takalar Regency, South Sulawesi. This study employed a Research and Development (R&D) approach with a quasi-experimental effectiveness test using a pretest–posttest control group design, involving 140 pregnant women (70 in the intervention group and 70 in the control group). Data were analyzed using paired t-tests to assess within-group pretest–posttest differences and independent t-tests to compare outcomes between the intervention and control groups. Validation results indicated that the module was highly feasible (mean score: 4.64). After the intervention, knowledge increased from 60.75 to 85.60 and attitudes from 70.25 to 91.40 in the intervention group. Statistical tests showed a significant difference (p<0.000) compared to the control group. In conclusion, the CAMPE Module proved to be effective and significantly improved the knowledge and attitudes of high-risk pregnant women regarding preeclampsia prevention. This module is appropriate for use as a local food–based nutrition education tool in primary healthcare services. Future multicenter randomized studies with longer follow-up periods are needed to evaluate long-term effectiveness and clinical outcomes.